Performance and kinetics of membrane and hybrid moving bed biofilm‐membrane bioreactors treating salinity wastewater. Issue 8 (9th March 2017) - Rodríguez‐Sánchez, Alejandro; Leyva‐Díaz, Juan Carlos; Poyatos, José Manuel; González‐López, Jesús
Abstract : A pilot‐plant membrane bioreactor (MBR) and two pilot‐plant hybrid moving bed biofilm reactor–membrane bioreactors (MBBR–MBRs), divided into three aerobic and one anoxic chambers, were started up for the treatment of salinity‐amended urban wastewater. The MBBR–MBR systems worked with and without carriers in the anoxic zone (MBBR–MBRanox and MBBR–MBRn/anox, respectively). The systems were operated from start‐up to stabilization, showing high removal of organic matter—a maximum of 90% chemical oxygen demand and 98% biochemical oxygen demand on the fifth day for MBBR–MBRn/anox in the stabilization phase—but low nitrogen elimination—30% maximum for MBBR–MBRn/anox in the stabilization phase. Biofilm attached to carriers reached less than 50 mg L −1 in the hybrid system. MBR showed faster kinetics than the two MBBR–MBR systems during start‐up, but the opposite occurred during stabilization. Maximum specific growth rates for heterotrophic and autotrophic biomass were 0.0500 and 0.0059 h −1 for MBBR–MBRn/anox in the stabilization phase. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3329–3342, 2017